Miles' Equation in Random Vibrations Theory and Applications in Spacecraft Structures Design - Wijker, Jaap (Solid Mechanics and Its Applications,, 2018)
This book discusses the theory, applicability and numerous examples of Miles' equation in detail. Random vibration is one of the main design drivers in the context of the design, development and verification of spacecraft structures, instruments, equipment, etc, and Miles' equation provides a valuable tool for solving random vibration problems. It allows mechanical engineers to make rapid preliminary random response predictions when the (complex) structure is exposed to mechanical and acoustical loads. The book includes appendices to support the theory and applications in the main chapters.